Analysis of the Spatial Changes in the Reed Stands of the Kis-Balaton Ingo-Berek Reed Beds Using Satellite Images and the Normalized Differentiated Vegetation Index (NDVI) - Soós, Gábor; Anda, Angéla (GEORGIKON FOR AGRICULTURE, 2024)
The reed (Phragmites australis) is the dominant macrophyte plant of Kis-Balaton, and in the case of the Kis-Balaton Water Conservation System (KBVR) it is estimated to cover an area of about 2000 ha. Wetland habitats such as Kis-Balaton are unimaginable not only in Hungary, but also in the whole world, without the presence of small or large coherent stands of reeds. The use of Landsat 8 satellite imagery as a remote sensing tool can help to identify changes in the vegetation of the Kis-Balaton. Analysis using the NDVI (Normalized Difference Vegetation Index) calculation method can provide information on the vegetation density of a given area. The main objective of our study is to determine the annual spatial variation and fragmentation of the reed stands in the Ingói-berek reed beds of Kis-Balaton from 2013 to 2023 by classifying Landsat 8 satellite data.
Keywords: remote sensing; vegetation change; fragmentation; NDVI